Transtracheal ultrasonography versus endtidal capnography in rapid confirmation of endotracheal tube placement - Shruthi Rioniz; Nischala Dixit; Preethi Rioniz; Thomas T Vellapally; Nayanthara Joachim; Siddhanth Suresh (Asian Journal of Medical Sciences)
Background: Prompt confirmation of proper endotracheal (ET) tube placement after intubation is imperative to averting life-threatening consequences. Waveform capnography, although the gold standard method, poses some limitations while transtracheal ultrasonography (USG) is a reliable real-time technique that has shown much promise. Existing literature on the faster method has yielded conflicting results.